Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1136/adc.2007.135889
|View full text |Cite
|
Sign up to set email alerts
|

Maternal versus fetal inflammation and respiratory distress syndrome: a 10-year hospital cohort study

Abstract: Maternal and fetal intrauterine inflammatory responses are both protective for RDS. The presence of chorioamnionitis with umbilical vasculitis is associated with a markedly greater reduction of RDS than chorioamnionitis alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 23 publications
(21 reference statements)
7
70
0
1
Order By: Relevance
“…Most of the recently published studies on choriamnionitis and BPD have not confirmed the effect of chorioamnionitis on BPD. Our results have shown no influence of CHA, neither funisitis or elevated levels of cytokines on BPD, but have also shown that prenatal exposure to CHA decreases incidence of RDS, results similar to other published data (20,21,22,23). Moss et al (24) showed in a sheep model that lung structure, function, and surfactant system were all significantly affected by the intra-amnioticaly given endotoxin at all stages of pulmonary development, but the response itself differed depending on the gestational timing.…”
Section: Resultssupporting
confidence: 93%
“…Most of the recently published studies on choriamnionitis and BPD have not confirmed the effect of chorioamnionitis on BPD. Our results have shown no influence of CHA, neither funisitis or elevated levels of cytokines on BPD, but have also shown that prenatal exposure to CHA decreases incidence of RDS, results similar to other published data (20,21,22,23). Moss et al (24) showed in a sheep model that lung structure, function, and surfactant system were all significantly affected by the intra-amnioticaly given endotoxin at all stages of pulmonary development, but the response itself differed depending on the gestational timing.…”
Section: Resultssupporting
confidence: 93%
“…47 Fetal signs of chorioamnionitis have been shown to have an additional effect on RDS reduction, suggesting a 'dose'-dependent response. 4 However, we have not been able to reproduce these findings. 8 Despite a reduction in acute respiratory problems, several early human studies have shown chorioamnionitis to be associated with a paradoxical increase in chronic lung disease of prematurity.…”
Section: Lungsmentioning
confidence: 80%
“…2 As a result, the proportion of preterm infants exposed to chorioamnionitis increases with decreasing gestational age to up to 80% below 28 weeks of gestation. 3,4 Ascending bacterial invasion of the uterine cavity is thought to be the most common route of infection, although bacteria are identified only in the minority of cases. 2 Organisms most frequently associated with chorioamnionitis are mainly of low virulence, including Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have demonstrated a reduction in the incidence of RDS in neonates with chorioamnionitis. 3,20 However, HC in the presence of RDS can alter the pulmonary protective effect of isolated chorioamnionitis, suggesting that complicated severe inflammation prevents modulation in premature infants. 21 Intrauterine exposure to proinflammatory cytokines or antenatal infection may prime the fetal lung such that minimally injurious postnatal events provoke an uncontrolled pulmonary inflammatory status that affects normal alveolarization and pulmonary vascular development.…”
Section: Discussionmentioning
confidence: 99%